Bifunctional liposomes reduce the chemotherapy resistance of doxorubicin induced by reactive oxygen species. (16th September 2019) - Xu, Lei; Zhang, Zhicheng; Ding, Yawen; Wang, Li; Cheng, Yali; Meng, Lingtong; Wu, Jinhui; Yuan, Ahu; Hu, Yiqiao; Zhu, Yishen
Abstract : A biofunctional liposome containing acriflavine (ACF) and doxorubicin (DOX) for reducing the chemotherapy resistance of DOX induced by reactive oxygen species. Abstract : Doxorubicin (DOX) liposome is a widely used nano-medicine for colorectal cancer treatment. However, doxorubicin therapy increases the level of reactive oxygen species (ROS) in tumor cells, such as hydrogen peroxide (H2 O2 ), which can stabilize hypoxia-inducible-factor-1α (HIF-1α). In a tumor hypoxic microenvironment, HIF-1 can up-regulate tumor-resistance related proteins, including P-glycoprotein (P-gp), glucose transporter 1 (GLUT-1), and matrix metalloproteinase 9 (MMP-9), leading to tumor tolerance to chemotherapy. The functional inhibition of HIF-1 can overcome this resistance and enhance the efficacy of tumor therapy. Here, we encapsulated one of the most effective HIF-1 inhibitors, acriflavine (ACF), and DOX in liposomes (DOX-ACF@Lipo) to construct bifunctional liposomes. ACF and DOX, released from DOX-ACF@Lipo, could effectively suppress the function of HIF-1 and the process of DNA replication, respectively. Consequently, the bifunctional liposome has great potential to be applied in clinics to overcome chemotherapy resistance induced by hypoxia.